A neurolinguistic theory of bilingualism - Paradis, Michel (Studies in bilingualism, 2004)
This volume is the outcome of 25 years of research into the neurolinguistic aspects of bilingualism. In addition to reviewing the world literature and providing a state-of-the-art account, including a critical assessment of the bilingual neuroimaging studies, it proposes a set of hypotheses about the representation, organization and processing of two or more languages in one brain. It investigates the impact of the various manners of acquisition and use of each language on the extent of involvement of basic cerebral functional mechanisms. The effects of pathology as a means to understanding th.